The Tartar Steppe: A Journey through a Limbo - Castelli, Alberto (Quaderni d'Italianistica)

(untitled) (Iter Press, 2022)
Dino Buzzati’s most famous text, The Tartar Steppe (1940), is not simply the story of a young officer dispatched to do service in a remote fortress overlooking a vast northern desert, but a continuous oscillation between chronicle and fabulous realism. The narrative elicits a feeling of sharp malaise, a sense of anguish similar to the one conveyed by existentialist philosophy and Kafka’s fiction. By comparing Buzzati’s novel to its progenitors, this essay depicts the central experience of its main character as a journey to the afterlife where people, objects, and landscapes are but projections of a spiritual limbo.